Tingkat Kepuasan Pasien Terhadap Pelayanan Rawat Jalan Di Rsud Kabupaten Majalengka - Gugun Priyadi; Mustara Mustara (FORIKES, 2022)
The level of outpatient satisfaction is the patient's feelings that arise as a result of the performance of the health services they get after the patient compares them with what they expect. So we need research that aims to describe the level of satisfaction of outpatients at Majalengka Hospital. This type of research is a descriptive study. The subjects of this study were 100 outpatients selected by incidental sampling technique. Data collection was carried out by filling out questionnaires, then analyzed descriptively. It is known that the scores for each dimension are: reliability = 72.75% (satisfied), responsiveness = 69.37% (satisfied), assurance = 76.35% (satisfied), empathy = 85.5% (very satisfied) and tangiables = 74.02% (satisfied). It is concluded that in general, outpatient services are satisfactory for patients.Keywords: outpatient; service quality; patient satisfaction ABSTRAK Tingkat kepuasan pasien rawat jalan adalah perasaan pasien yang timbul sebagai akibat dari kinerja layanan kesehatan yang diperolehnya setelah pasien membandingkannya dengan apa yang diharapkannya. Maka diperlukan penelitian yang bertujuan untuk mengetahui gambaran tingkat kepuasan pasien rawat jalan RSUD Majalengka. Jenis penelitian ini adalah studi deskriptif. Subyek penelitian ini adalah 100 pasien rawat yang dipilih dengan teknik incidental sampling. Pengumpulan data dilakukan melalui pengisian kuesioner, lalu dianalisis secara deskriptif. Diketahui bahwa skor masing-masing dimensi adalah: reliability = 72,75% (puas), responsiveness = 69,37% (puas), assurance = 76,35% (puas), empathy = 85,5% (sangat puas) dan tangiables = 74,02% (puas). Disimpulkan bahwa secara umum, pelayanan rawat jalan adalah memuaskan pasien.Kata kunci: rawat jalan; kualitas pelayanan; kepuasan pasien